The Correlation between Ultra-Processed Food Consumption and Increased Risk of Chronic Disease in the Context of a Modern Lifestyle - Ramadhani, Firdausi (Oshada, 2025)
Changes in food consumption patterns in the urbanization era have increased the proportion of ultra-processed foods (UPFs) in the daily diet, which is associated with an increased prevalence of chronic diseases. This study aims to analyze the relationship between UPF consumption and the risk of chronic diseases in the context of modern lifestyles in Indonesia. The study design used a quantitative cross-sectional approach in 420 respondents aged 20–59 years in urban areas, who were selected purposively. Data were collected through the NOVA classification-based Food Frequency Questionnaire, the International Physical Activity Questionnaire, the Perceived Stress Scale, and examinations of chronic disease risk indicators by health workers. Analysis was performed using multivariate logistic regression. The results showed that high UPF consumption increased the risk of chronic diseases by 4.66 times compared to low consumption (p<0.001). Other significant factors included low physical activity (OR=2.42 ) , poor sleep patterns (OR=1.91), high stress (OR=2.05), age ≥40 years (OR=2.31), smoking (OR=1.96), and family history of disease (OR=2.48). Gender and socioeconomic status were not significant. In conclusion, high UPF consumption, exacerbated by unhealthy lifestyle behaviors , significantly increases the risk of chronic disease. Comprehensive public health interventions are needed, including nutrition education, physical activity promotion, stress management, and UPF marketing controls.